2013
DOI: 10.4103/2278-330x.105861
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant melanoma of the vagina: A case report and review of literature

Abstract: A 60 year old woman presented in gynecology department with bleeding per vagina and subsequently histotpathologically, it was diagnosed as malignant melanoma of the vagina. She underwent excision biopsy. On metastatic work-up, Positron emission tomography (PET) scan proved that she had distant metastasis and received palliative radiotherapy and chemotherapy, with temozolamide. She is alive after one year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
1
9
0
1
Order By: Relevance
“…The concern of possible vulvar melanoma, although rare, was warranted because it is an aggressive tumor that accounts for less than 1% of all malignant melanomas and carries a poor prognosis, with a 5-year survival rate of 5% to 25%. 7 , 8 After the patient's dermatology referral visit and subsequent discussion between dermatology, dermatopathology, and gynecology departments, this patient's biopsy slides were re-examined with iron staining, which showed the minocycline deposition. The patient was give assurance that her vulvar pigmentation was not melanoma and would not require further biopsies or a complete resection.…”
Section: Discussionmentioning
confidence: 99%
“…The concern of possible vulvar melanoma, although rare, was warranted because it is an aggressive tumor that accounts for less than 1% of all malignant melanomas and carries a poor prognosis, with a 5-year survival rate of 5% to 25%. 7 , 8 After the patient's dermatology referral visit and subsequent discussion between dermatology, dermatopathology, and gynecology departments, this patient's biopsy slides were re-examined with iron staining, which showed the minocycline deposition. The patient was give assurance that her vulvar pigmentation was not melanoma and would not require further biopsies or a complete resection.…”
Section: Discussionmentioning
confidence: 99%
“…We included this case study in this article because of primary origin in vaginal mucosa which is quite rare. It occurs in less than 1% of all malignant melanomas and less than 3% of all primary malignant tumors of the vagina [ 6 ]. Contemporary treatment of malignant melanoma includes surgery, radiotherapy and systemic therapy with chemo- and immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Response is observed in only 15% of patients [ 3 , 6 ]. Adjuvant therapy with interferon α-2b should be considered on a case-by-case basis [ 6 ]. A promising option seems to be immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study by the Gynecologic Oncology Group spanning 17 years recorded only 43 such cases (10). The annual estimated incidence of primary malignant vaginal melanoma is 0.026 per 100,000 women (7) and 0.46 per one million women (8). A statistical analysis by Shah et al on the epidemiology of malignant vaginal cancer indicated that among the 2.531 cases taken under study, non-Hispanic Whites constituted 66% of the registered cases (11); African American women, Hispanic women, Asian/Pacific Islanders and others constituted 14%, 12%, 7% and 1% of the total number of malignant vaginal cancer cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no effective treatment strategy yet in place (8), the current treatment plan includes wide local excision (WLE), radical surgery, chemotherapy, immunotherapy, combination therapeutics and palliative care (3). Radiotherapy is used as adjuvant therapy, as data suggest that radiotherapy does not bring overall benefit as sole therapy (9).…”
mentioning
confidence: 99%